2020
DOI: 10.3390/su12093513
|View full text |Cite
|
Sign up to set email alerts
|

Role of Integrated Nutrient Management and Agronomic Fortification of Zinc on Yield, Nutrient Uptake and Quality of Wheat

Abstract: Phosphorus (P) and zinc (Zn) are essential plant nutrients, and their deficiency in soils and the antagonistic effect of P on Zn are important concerns world-over. Thus, a two-year (2012–13 to 2013–14) experimentation was carried out to assess grain yield, nutrient uptake and quality parameters of wheat by various levels of P and Zn. The results revealed that 50% recommended dose of P (RDP) through phospho-enriched compost (PEC) + 50% RDP through fertiliser and soil application of 12.5 kg ZnSO4.7H2O ha−1 + one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
4
18
0
Order By: Relevance
“…The application of 50% RDF + 50% RDN through FYM increased the amount of available N to 100% RDF during both years. This could be explained by the residual effect of decomposed organic manure within the soil following crop harvest [40]. Su et al [41], Jiang et al [42], and Dass et al [43] have also confirmed that FYM application separately or combined with some inorganic fertilizer enhanced the nutrient composition of the soil.…”
Section: Available Nutrient Status In the Soil At The Harvestmentioning
confidence: 89%
“…The application of 50% RDF + 50% RDN through FYM increased the amount of available N to 100% RDF during both years. This could be explained by the residual effect of decomposed organic manure within the soil following crop harvest [40]. Su et al [41], Jiang et al [42], and Dass et al [43] have also confirmed that FYM application separately or combined with some inorganic fertilizer enhanced the nutrient composition of the soil.…”
Section: Available Nutrient Status In the Soil At The Harvestmentioning
confidence: 89%
“…With respect to nutrient management in aromatic rice, significantly taller plant height was noted with 50% RDF + 50% RDN through FYM in both the years which was at par with 75% RDF + green manuring and 75% RDF + 25% RDN through FYM. It might be due to the reason that integrated nutrient management practices increased in higher nutrient availability, resulting in increased conversion of carbohydrates to protein, which enhances meristematic cellular activity like cell division and cell elongation expressing morphologically in terms of increasing measured variables—such as plant height—ultimately increasing higher dry matter accumulation [ 23 , 24 , 25 ]. Similar results were also obtained by Asewar et al [ 26 ], Sudha and Chandini [ 27 ] and Usman et al [ 28 ], who observed increasing growth attributes with FYM + chemical fertiliser applied plots.…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to the genesis of insoluble forms of Cu, such as Cu-phosphate. Paramesh et al [66] reported application of P through chemical fertilizer or compost significantly increased the Fe concentration and uptake in wheat [66]. Among the Si applications, the highest Fe and Mn uptake in grain and straw was recorded with 120 kg Si ha -1 .…”
Section: Zn Fe Mn and Cu Uptakementioning
confidence: 99%